PENGEMBANGAN BAHAN AJAR BERBASIS MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS III DI SEKOLAH DASAR - Neng Nisa Noer Restui, - (2020)
ABSTRACK This research was motivated by mind mapping based teaching materials to improve the speaking skills of third grade students in elementary schools. The research method used in carrying out this research is the Development Research method by Richey, Klein and Nelson which was developed from the D&D research method with the model used, namely DDE (Design, Development, and Evaluation) using questionnaire instruments and literature study. The data analysis used a Likert scale. The development of teaching materials is carried out in three stages, namely the design stage by analyzing problems in the field such as student needs analysis, learning analysis and concept analysis, and formulating learning objectives, the development stage, and the formative evaluation stage. The resulting teaching material is the development of mind mapping-based teaching materials in improving the speaking skills of third grade students in elementary schools. The feasibility of developing mind mapping-based teaching materials based on the results of the assessment of teaching material media experts and learning practitioners in elementary schools is considered to be very good. Meanwhile, according to the expert lecturer, the learning material is considered good if it is used as learning material in improving speaking skills in grade III students in elementary schools. The student speaking skill assessment sheet based on the results of the assessment of learning experts in elementary schools is very feasible when used as a tool to measure the assessment of students' speaking skills in the development of learning tools in the form of mind mapping-based teaching materials. In the development of teaching materials, it must contain psychological and sociological aspects. Because both of them will meet and be connected to each other. As for the development of this teaching material, it would be better if it was implemented directly in the field so that it could prove the accuracy of the development data in improving the speaking skills of third grade students in elementary schools. Keywords: teaching material development, mind mapping, speaking skills.